ІГРОВА ДІЯЛЬНІСТЬ В СИСТЕМІ ПІДГОТОВКИ СТУДЕНТІВ ВИЩИХ ПЕДАГОГІЧНИХ ЗАКЛАДІВ ДО ІНШОМОВНОГО СПІЛКУВАННЯ (Педагогіка вищої та середньої школи, 2004)
The article shows the essence of the students' playing activity during their foreign language communication training. The author gives the examples o f using some kinds of games in practice and demonstrates the effectiveness of using playing activities of students as prospective teachers in order to prepare them to foreign communication.